Pharmacological evidence for connection of nitric oxide-mediated pathways in neuroprotective mechanism of ischemic postconditioning in mice - Puja Gulati; Nirmal Singh (Wolters Kluwer Medknow Publications, 2014)
Introduction: Postconditioning (PoCo) is an adaptive phenomenon whereby brief repetitive cycles of ischemia with intermittent reperfusion instituted immediately after prolonged ischemia at the onset of prolonged reperfusion elicit tissue protection. PoCo is noted to exert a protective effect in various organs like heart, liver, kidney and brain. Various triggers, mediators and end effectors are suggested to contribute to the protective effect of PoCo. However, the neuroprotective mechanism of PoCo is poorly understood. Objectives: The present study has been designed to investigate the role of nitric oxide pathway in the neuroprotective mechanism of ischemic postconditioning (iPoCo) employing a mouse model of global cerebral ischemia and reperfusion-induced injury. Materials and Methods: Bilateral carotid artery occlusion (BCAO) of 12 min followed by reperfusion for 24 h was employed to produce ischemia and reperfusion (I/R)-induced cerebral injury in mice. Cerebral injury was assessed in the terms of cerebral infarct, memory impairment and motor in-coordination. Brain nitrite/nitrate; acetylcholinesterase activity, thiobarbituric acid reactive species (TBARS) and glutathione level were also estimated. Results: BCAO followed by reperfusion produced a significant rise in cerebral infarct size, memory impairment and motor incoordination. Further a rise in acetylcholinesterase activity and TBARS level along with fall in brain nitrite/nitrate and glutathione levels was also noted. iPoCo consisting of three episodes of 10 s carotid artery occlusion and reperfusion (instituted immediately after BCAO) significantly attenuated infarct size, memory impairment, motor incoordination as well as altered biochemicals. iPoCo-induced neuroprotective effects were significantly abolished by pretreatment of L-NAME, a nonselective NOS inhibitor. Conclusion: It may be concluded that the nitric oxide pathway probably plays a vital role in the neuroprotective mechanism of iPoCo.